Menanggulangi Masalah Kemiskinan dan Pengangguran di Indonesia dalam Perspektif Ekonomi - - Purwanto (Jurnal Ekonomi dan Pendidikan, 2005)
Problems of macro economy that related to peoples life are often called twin problems. The aimed problems are the poverty and unemployment matters. The two problems are very interesting to discuss in order to solve them. Poverty and unemployment happened in relation to the rate or the condition of economic growth, thus there are three important things should be concerned with in this efforts of overcoming the poverty, as following: firstly, the economic growth that offered benefit as great as possible for poor people. Secondly, the development of social community is by extending and stimulating the nature and potency of individual who were independent, creative, and innovative. It shall encourage the creation of partnership forms between middle economic society, stronger economic society toward poor society. This effort would not be conferred freely, however, by giving motivation, working program and the way to finish/ accomplish it. The expectation of this model aimed at forming autonomous society, free from dependence on other people. Thirdly, the system of clean and respected government, commitment to policies determined before. Eventually, the problems of poverty and unemployment might be like tragedies of Indonesian people, tragedy of Indonesian economy, and there had not been effective medicine to recover our economic collapse. Liberal thoughts with their materialistic, egoistic, and greedy natures have dominated and defeated moralistic and brotherhood thoughts. Through economic reformation we shall build the unity of Indonesia to achieve the equality of rational and fair revenue. The economic reformation should be defined as the awareness of their mistakes and the awareness to correct them.